A study of separation of powers with special reference between the executives and judiciary in Malaysia / Tun Saiful Aman Zakaria ...[et al.] - Zakaria, Tun Saiful Aman; Abdul Wahab, Bashirah; Idris, Mohd Shahrom; Mohamed Amin, Nurul Farhana; Abdul Rahman, Nurul Shida (2010)
This project attempts to identify the effectiveness of Separation of Powers practice in Malaysia between Executives and Judiciary. Data were gathered from questionnaires, interviews and observation of and participation in lectures, seminars and tutorials. The report concludes that there exists interference in the separations of powers apply in Malaysia. From the survey, we found that most of them agreed that there is interference from the executive in judiciary. This research is to see whether the theoretical of which many of people, books and newspaper and articles have said and claimed of the overlapping of powers between the Executive and the Judiciary. Hence, the research is conducted to identify the actual situation that creates the assumptions of the ineffectiveness application which it is a controversial issue that is usually spoken in the cafe's and nets.